Imunidades tributárias: imunidades tributárias e os tributos vinculados - Brito, Sávio Ramsés Andrade (2004)
Unquestionable is the necessity of the modem State to institute tributes to maintain its machine and suppliers of the necessaiy subsidies to the accomplishment of its inherent activities, as well as those indispensable ones to the persecution of the common good. In order to accomplish this, the Constitution of the Brazilian Federative Republic delineated our tributaiy system, of where comes the institute of the immunity tax. The immunities are nothing more then the recognition, by a State Constitution. of the necessity to protect certain basic principies of the regimen and the preservation of detemuned ethical and cultural values, not recognizing, therefore, the ability for the creation of tributes, forbidding it. Special circumstances are those that the constituent chooses as deserving immunity tax. As so. ahead of the relevance of this institute, the adequate interpretation of the immunity norms becomes indispensable, in order not to tax certain people, good or activities, that had constitutionally remained protected of the imposing-tax activity of the federative entities. Doctrinal questioning appears in the application of the immunity institute of the tied tributes, as per that these are result of specific State activity related to the contributor, being that a reason to imagine that the immunities taxes would not reach such hypotheses of taxation. Therefore, in this paper it is made a study about the immunities taxes.